Effect of Plant Proteins in Iso-caloric Feeds on Growth Performance of Freshwater Prawn Macrobrachium idae (Heller) - M.A., Haniffa; T.A., Sethuramalingam; S., Arul Selvan; A., Jesu Arockia Raj (Fishery Technology, 2025)
Macrobrachium idae juveniles (0.9 - 1.3 g) were fed on eight formulated diets containing 32-42% crude protein to assess their growth performance. Prawns fed on groundnut oil cake meal (GOC) and soybean meal (SBM) showed the best growth rate (SGR) (0.46 and 0.43%.day"1, respectively), food conversion ratio (FCR) (2.16 and 2.53, respectively) and protein efficiency ratio (PER) (0.84 and 0.78, respectively). Hydrilla verticellata (HV) and drumstick leaves (DRM) diets resulted in poor growth and decreased PER and SGR with elevated FCR. The efficiency of absorption and net conversion ranged between 84-90% and 3.81-7.8%, respectively. Increase in dietary protein content (3-8%) produced elevated growth rates and protein efficiency ratio. The dietary protein-energy ratio for maximum growth of prawns was 97.2 mg.kcal"1 with a digestible energy of 431 kcal.lOOg-1 of feed.